Hindustani Music - Ahmad, Najma Perveen (Brill | Manohar Publishers & Distributors, 2024)
During the Medieval period, Indian Music went through a meta¬morphosis, blending in itself beautifully the Arab, Persian, and Central Asian influences, and which gave birth to new forms and styles which continue to survive even today. Dr. Najma Perveen Ahmad has analysed the development of Hindustani Music during the seventeenth and eighteenth centuries ad and has studied such texts as Raag Darpan, Tohfat-ul-Hind, Usulun-Naghmat-e-Aasifi and Naadirat-e-Shahi. What she provides in the pages of the book is an authentic survey of music during the seven-teenth and eighteenth centuries, and its impact on contemporary Hindustani Music. Development of forms and styles like Dhruvapada, Khayal, and many Ragas have been gone into in their minutest details. Profiles of musicians during that time and their contemporary musical traditions add great value to this well-researched study.